Ireland and the British Empire essays on art and visuality - Cullen, Fintan 1954- (Peter Lang, 2023)
«This dazzling collection of essays draws out the complexity of Ireland’s connections with British imperialism.　The volume takes an admirably wide-ranging and generous approach to Irish visual culture, showing how features such as Irish fashion, architecture, and museum display have been affected by empire.　Those interested in Irish art, in Irish culture, and in the legacies of imperialism more generally will find this book insightful, illuminating, and provocative.»(James Moran, Professor of English, University of Nottingham)　«Ranging across a broad chronological span, this stimulating collection’s focus on the role of the British empire within Irish art and visuality is much-needed. This book will be invaluable not just for scholars of Irish culture, but for the study of the crucial significance of the visual in the historical formation of empire more generally.»(Fionna Barber, Reader in Art History, Manchester Metropolitan University)This collection of essays discusses how the British empire resonates in a huge array of visual culture in Ireland from the late eighteenth century to the middle of the twentieth. The book is about the way empire has pervaded and continues to pervade Irish art and visual culture. The collection of essays expands the analysis of things visual in terms of Ireland and the British empire to include a broad range of cultural matter: art exhibitions, museums and their displays, architecture, photography, illustrated books, fashion, public and private performances and entertainments, as well as paintings, sculpture, prints and book illustration. The essays only touch on some of the issues that need to be discussed in relation to Ireland and the visual culture of imperialism, but it is hoped that this volume will spark others to investigate the topic and thus greatly expand Irish visual historiography.
Keywords: Geschichte; Bildmaterial; Imperialismus; Kunst; Irland; Großbritannien; Aufsatzsammlung